Pengaruh Satisfaction, Serqual, Value, Trust, Switch cost, Corpimage Terhadap Customer Loyalty - Marcellinus Marcellinus; Tommy Setiawan Ruslim (Jurnal Manajerial Dan Kewirausahaan, 2019)
This study aims to determine the effect of customer satisfaction, perceived service quality, perceived value, trust, perceived switching costs, and corporate image of customer loyalty. This study uses the reference theory of "Theory of Reasoned Action" and "Theory of Planned Behavior". Subjects / respondents of the research used were students of the Faculty of Economics, Tarumanagara University who were still actively studying. The sampling technique used is non-probability sampling with the criteria of purposive sampling. The number of samples used in this study is 139 respondents obtained by distributing questionnaires online through the google form. After the data is collected, it will be processed using IBM SPSS version 24.0 software. The period of this study was carried out in a cross-sectional study. The results of data processing show that customer satisfaction has a positive and significant effect on customer loyalty, perceived service quality has a positive and significant effect on customer loyalty, perceived value has a positive and insignificant effect on customer loyalty, trust has a positive and significant effect on customer loyalty, perceived switching costs have an effect positive and significant for customer loyalty, and corporate image has a positive and insignificant effect on customer loyaltyPenelitian ini bertujuan untuk mengetahui pengaruh customer satisfaction, perceived service quality, perceived value, trust, perceived switching costs, dan corporate image terhadap customer loyalty Penelitian ini menggunakan acuan teori “Theory of Reasoned Action” dan “Theory of Planned Behavior”. Subjek / responden penelitan yang digunakan adalah mahasiswa Fakultas Ekonomi Universitas Tarumanagara yang masih aktif kuliah. Teknik pengambilan sampel yang digunakan adalah non-probability sampling dengan kriteria purposive sampling. Jumlah sampel yang digunakan dalam penelitian ini adalah 139 responden yang diperoleh dengan penyebaran kuesioner secara online melalui google form. Setelah data dikumpulkan, akan diolah menggunakan software IBM SPSS versi 24.0. Periode penelitian ini dilakukan secara cross sectional study. Hasil pengolahan data menunjukkan bahwa customer satisfaction berpengaruh positif dan signifikan terhadap customer loyalty, perceived service quality berpengaruh positif dan signifikan terhadap customer loyalty, perceived value berpengaruh positif dan tidak signifikan terhadap customer loyalty, trust berpengaruh positif dan signifikan terhadap customer loyalty, perceived switching costs berpengaruh positif dan signifikan terhadap customer loyalty, dan corporate image berpengaruh positif dan tidak signifikan terhadap customer loyalty.